1990
DOI: 10.1210/endo-126-1-451
|View full text |Cite
|
Sign up to set email alerts
|

Development and Use of a Mathematical Two-Pool Model of Distribution and Metabolism of 3,3′,5-Triiodothyronine in a Recirculating Rat Liver Perfusion System: Albumin Does not Play a Role in Cellular Transport*

Abstract: To describe the T3 kinetics in a recirculating rat liver perfusion system, we have developed a mathematical two-pool model consisting of medium and liver. It appeared that all parameters of the model could be fully resolved by using the time-dependent disappearance of radioactive T3 (2 nM) from the medium only. The model calculates the T3 medium pool, the T3 liver pool, and the amount of hormone metabolized at different times after the start of the perfusion. To check the validity of the model, metabolism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…134). Similar to the results in cultured rat hepatocytes, we found that, in addition to the energy state of the liver, the free hormone concentration in the perfusion medium determined the amount of hormone taken up by the intracellular compartment of the liver (135). Studies using livers from amiodarone-treated animals indicated that transport of T., but not of T3, was inhibited (136), in agreement with hepatocyte studies (47,55) showing that T. and T3 are transported differently across the liver plasma membrane.…”
Section: A Transport Into the Liversupporting
confidence: 85%
“…134). Similar to the results in cultured rat hepatocytes, we found that, in addition to the energy state of the liver, the free hormone concentration in the perfusion medium determined the amount of hormone taken up by the intracellular compartment of the liver (135). Studies using livers from amiodarone-treated animals indicated that transport of T., but not of T3, was inhibited (136), in agreement with hepatocyte studies (47,55) showing that T. and T3 are transported differently across the liver plasma membrane.…”
Section: A Transport Into the Liversupporting
confidence: 85%
“…134). Similar to the results in cultured rat hepatocytes, we found that, in addition to the energy state of the liver, the free hormone concentration in the perfusion medium determined the amount of hormone taken up by the intracellular compartment of the liver (135). Studies using livers from amiodarone-treated animals indicated that transport of T 4 , but not of T 3 , was inhibited (136), in agreement with hepatocyte studies (47,55) showing that T 4 and T 3 are transported differently across the liver plasma membrane.…”
Section: A Transport Into the Liversupporting
confidence: 85%
“…Livers of male Wistar rats (200-250 g) were isolated and perfused in a recirculating system at 37°C as described previously. [9]. The magnetically stirred perfusion medium used in all experiments was 150 ml KrebsRinger buffer (ll8mmol/1 NaC1, 5retool/1 KC1, 1.1 mmol/l MgSO 4, 2.5 mmol/1 CaC12, 1.2 mmol/1 KHzPO 4, and 25 mmol/1 NaHCO3) supplemented with 10 mM glucose and 1% BSA.…”
Section: Radiolabelling and Quality Control Of The Radiopharmaceuticalmentioning
confidence: 99%